Influence of Renal Function on the Single‐Dose Pharmacokinetics of Besifovir, a Novel Antiviral Agent for theTreatment of Hepatitis B Virus Infection. (17th September 2021) - Hwang, Jun Gi; Kim, Yu Kyong; Choi, Young‐sim; Kwon, Soon Kil; Han, Joung‐Ho; Park, Min Kyu
Abstract: Per the well‐known resistance of hepatitis B virus to nucleoside/nucleotide analogs, alternative treatment options with higher resistance barriers have been approved for use in both treatment‐naïve and lamivudine‐resistant hepatitis B virus infections. This phase I study was conducted in adults with normal and impaired renal function to evaluate the effect of renal impairment on the pharmacokinetics of besifovir, a prodrug of an acyclic nucleotide phosphonate, that is mainly cleared via renal excretion. An open‐label, single‐dose parallel‐group clinical study was conducted in subjects with normal renal function and mild, moderate, and severe renal impairment. Subjects received a single oral dose of besifovir dipivoxil 150 mg, and serial blood and urine samples were collected for up to 72 hours after dosing to assess the pharmacokinetic characteristics of besifovir. The extent of plasma exposure of besifovir, detected as its major and active metabolites, LB80331 and LB80317, respectively, increased with worsening renal function. Compared to the subjects with normal renal function, the mean areas under the concentration‐time curves of LB80331 increased by 1.5‐, 2.5‐, and 4.5‐fold in subjects with mild, moderate, and severe impairment, respectively. LB80317 showed a 1.8‐, 3.2‐, and 6.2‐fold increase in subjects with mild, moderate, and severe renal impairment compared to those with normal function. The ratios of LB80331 renal clearance and the average estimated glomerular filtration rate of each renal impairment group with respect to the normal group were similar. The increase in plasma exposure and decrease in renal clearance suggest the need to adjust dosage regimens in patients with moderate to severe renal impairment.